Seasons of Grace : The Missing - Book 2 - Lewis, Beverly 1949- (Minneapolis : Bethany House Publishers, 2009)
Longing to find her missing mother and uncover the secrets that led to her leaving three weeks earlier, Grace befriends the non-Amish Heather, and the two travel together in hopes of finding Grace's mother and bringing her home.
Keywords: Amish -- Fiction; Secrecy -- Fiction; Fiction; Love stories